Análisis y Propuesta de Mejora de un Sistema de Precarga Para los Rodamientos de los Reductores Delanteros en los Tractores CASE PUMA (2023)
There are various types and brands of tractors on the market, used by different companies in the agricultural sector. Their functions vary depending on their size, class, and brand. CASE PUMA tractors are used in the company's production process, such as sugarcane lifting and harvesting, land preparation, and other tasks. The following project shows the analysis and improvement proposal for a preload system for the bearings of the front reduction gears of CASE PUMA tractors. This is intended to provide a new design that will extend the machine's lifespan and reduce maintenance and repair costs.